XDR TB in South Africa - What lies ahead? - V. Thaver; Gboyega A. Ogunbanjo (South African Family Practice)
The emergence of XDR TB coupled with the high prevalence of HIV/AIDS has intensified the need to identify new treatment strategies and accelerate research into antibiotics against XDR TB before the world is faced with a global public health crisis. This article gives a short overview on the important health implications of XDR-TB in South Africa.